If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(3x + 6) = 240 Reorder the terms: x(6 + 3x) = 240 (6 * x + 3x * x) = 240 (6x + 3x2) = 240 Solving 6x + 3x2 = 240 Solving for variable 'x'. Reorder the terms: -240 + 6x + 3x2 = 240 + -240 Combine like terms: 240 + -240 = 0 -240 + 6x + 3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-80 + 2x + x2) = 0 Factor a trinomial. 3((-10 + -1x)(8 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-10 + -1x)' equal to zero and attempt to solve: Simplifying -10 + -1x = 0 Solving -10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 0 + 10 -1x = 0 + 10 Combine like terms: 0 + 10 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10Subproblem 2
Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8Solution
x = {-10, 8}
| 4x(x-2)=8x^2-9x | | X-10/3=-37 | | (2s)/3-(26-s)/5=0 | | (x)3x+6=240 | | 4x*7=5 | | x+2.3=-4.1 | | 367+12x=280+15x | | (4+m)/7=30 | | 3x+6(x)=240 | | 3x^1/3+2x^2/3-5=0 | | 18.9/2.1 | | 5v+27+4v=9 | | 3x+6*x=240 | | 3*y-5=-3 | | 14/11y+1/2=9/2 | | 3/x-15=-7 | | x^3+3X^2-33x=35 | | 16m+112=416 | | (5n+2)/3+(12-5n)/2=5 | | 76.50=.45b | | 3x^1/3+2x^2/3=0 | | -6y-7y-27=38 | | 11x/6-12=x/2+20 | | (3i+6)/11=(2i+3)/7 | | 35n-154=336 | | 3h-1=0 | | (2x+5x+10+4x+16)/(3x+18)=3 | | x^3+3X^3-33x=35 | | y+5=3/5 | | 3/2-2/5 | | 6=z-6 | | -16x+-14+5-5x= |